Diagnostic Efficacy of Plasma Urokinase-type Plasminogen Activator and Plasminogen Activator Inhibitor-2 in Differentiation of Hepatocellular Carcinoma from Cirrhosis - Song, Kyung Soon; Lee, Anna; Choi, Jong Rak; Kwon, Oh Hun (Thrombosis and Haemostasis, 1995)
We determined the plasma antigen levels of urokinase-type plasminogen activator(u-PA) and plasminogen activator inhibitor 2(PAI-2) in 41 patients with hepatocellular carcinoma and 28 patients with different stages of liver cirrhosis. No significant differences of u-PA and PAI-2 levels were calculated between the two groups of tumor patients (HCC) and liver cirrhosis without tumor (non-HCC).Within both study groups, no significant differences were found in u-PA and PAI-2 levels of the different Child categories. Discriminative functions of both u-PA and PAI-2 (total error count estimates of 43.1% and 43.6%, respectively), were low compared to that (29.0%) of alpha-fetoprotein (AFP). The combinations of AFP and u-PA lowered the total error rate (21.9%) more than that of each marker alone. However, whether plasma u-PA and PAI-2 may be considered as a risk factor further investigation was needed and our findings raise the question as to whether these markers could be considered as useful screening markers for earlier detection of HCC in liver cirrhosis because discriminant functions of u-PA and PAI-2 were not significant.Sensitivities and specificities of u-PA and PAI-2 were also not high enough, resulting in the ranges of total diagnostic efficiency from 43% to 50%, and, from 49% to 63% , respectively, at different cut-off values. No direct relationship was detected between AFP and u-PA, between AFP and PAI-2, and between u-PA and PAI-2.